Challenges and recent developments in hearing aids: part II. Feedback and occlusion effect reduction strategies, laser shell manufacturing processes, and other signal processing technologies. - Chung K (Trends in Amplification, 2004)
This is the second part of a review on the challenges and recent developments in hearing aids. Feedback and the occlusion effect pose great challenges in hearing aid design and usage. Yet, conventional solutions to feedback and the occlusion effect often create a dilemma: the solution to one often leads to the other. This review discusses the advanced signal processing strategies to reduce feedback and some new approaches to reduce the occlusion effect. Specifically, the causes of three types of feedback (acoustic, mechanical, and electromagnetic) are discussed. The strategies currently used to reduce acoustic feedback (i.e., adaptive feedback reduction algorithms using adaptive gain reduction, notch filtering, and phase cancellation strategies) and the design of new receivers that are built to reduce mechanical and electromagnetic feedback are explained. In addition, various new strategies (i.e., redesigned sound delivery devices and receiver-in-the-ear-canal hearing aid configuration) to reduce the occlusion effect are reviewed. Many manufacturers have recently adopted laser shell-manufacturing technologies to overcome problems associated with manufacturing custom hearing aid shells. The mechanisms of selected laser sintering and stereo lithographic apparatus and the properties of custom shells produced by these two processes are reviewed. Further, various new developments in hearing aid transducers, telecoils, channel-free amplification, open-platform programming options, rechargeable hearing aids, ear-level frequency modulated (FM) receivers, wireless Bluetooth FM systems, and wireless programming options are briefly explained and discussed. Finally, the applications of advanced hearing aid technologies to enhance other devices such as cochlear implants, hearing protectors, and cellular phones are discussed.